Ecologically minded teaching. Issue 8 (3rd August 2018) - McConnell Moroye, Christy; Ingman, Benjamin C.
Abstract: This study builds upon ongoing research of ecological mindedness by exploring how teachers appraise and incorporate ecological care, interconnectedness, and ecological integrity into lesson planning, as well as how teachers reconcile these qualities with their current professional responsibilities. These topics are explored through educational connoisseurship and criticism, using think alouds to learn from teachers as they plan lessons with the qualities of ecological mindedness as a framework. Findings indicate that teachers view ecological mindedness as relevant for schools in terms of content, engagement, and students' lives; as compatible with standards and other external mandates; and as a form of character education.